Chemometric approach for fast analysis of prometryn in human hair by GC–MS. Issue 14 (24th June 2013) - Yu, Weiwei; Cai, Wensheng; Shao, Xueguang
<x xml:space="preserve">Abstract</x> A method for the fast analysis of a specific component in complex samples by GC–MS was developed and used for the quantitative determination of prometryn in hair samples. In this method, the tedious and time‐consuming sample pretreatment for purification was avoided, and a short capillary column and fast temperature program were employed to speed up the analysis. Although the measured total ion chromatogram is composed of overlapping peaks with interference and background noise, the signal of prometryn can be extracted by chemometric methods. Window‐independent component analysis was used to extract the mass spectrum and a non‐negative immune algorithm was employed to obtain the chromatographic profile of the interesting component from the measured data. Due to the complexity of the matrix, a standard addition method was adopted for the quantification. The applicability of the method was validated with spiked samples, and the recoveries were in the range of 99–105%.